THE ALIGNMENT OF ORGANISATIONAL CULTURE WITH STRATEGIC INTENT - Dickson, Alan Ernest (My University, 2011)
A critical component in the implementation of strategy in South African business is the correct alignment of organisational culture with strategic intent. South Africa’s unique history may have created organisational cultures that do not support the strategies necessary for remaining competitive in the complex and rapidly changing global environment. This research was aimed at determining the alignment of organisational culture with strategic intent in South African organisations. Senior executives from 34 organisations completed a structured questionnaire. Descriptive statistics were utilised to determine each organisation’s strategic intent and organisational culture. Inferential statistics were performed for evaluating the alignment of the culture with strategic intent. The analysis of the sampled data indicated no statistically significant relationship between the measured organisational culture and the stated strategic intent. The findings highlighted the challenges associated with the measurement of strategic intent and the difficulty of applying international literature to the South African business environment. Evidence emerged that indicated a prevalence of differentiation generic strategies supported by organic cultures within the sampled organisations. A set of recommendations to improve the knowledge surrounding the alignment of organisational culture with strategic intent has been compiled.
MBA - WBS
Keywords: Organisational culture; Strategy